Hubungan Antara Binge-Watching Terhadap Prokrastinasi Akademik pada Mahasiswa yang Sedang Menyusun Skripsi di Jakarta - Stevani Stevani; Meiske Yunithree Suparman (LPPM Institut Pendidikan Nusantara Global, 2026)
Academic procrastination is the intentional delay of academic tasks or responsibilities until deadlines draw near, even when individuals are aware of the negative consequences of such postponement. For final-year university students working on their thesis, high academic pressure often triggers avoidance behaviors through leisure activities, one of which is binge-watching. This study examines the relationship between binge-watching habits and academic procrastination among university students. The purpose of this research is to determine whether there is a relationship between binge-watching activities and the level of academic procrastination. The participants in this study were final-year students who were actively working on their thesis at universities located in the Jakarta area. The research used a non-experimental correlational design. A total of 100 students from various universities in Jakarta were recruited using purposive sampling. The instruments used were the Binge-Watching Engagement Scale Questionnaire (BWESQ) and the Academic Procrastination Scale (APS). Data processing was carried out using SPSS version 25.0. The results of the Pearson Product-Moment correlation analysis showed a correlation coefficient of 0.086 with a significance value of 0.393 (p > 0.05). This indicates that there is no significant relationship between binge-watching and academic procrastination among final-year university students.